TRIF Mediates Toll-Like Receptor 2-Dependent Inflammatory Responses to Borrelia burgdorferi - Petnicki-Ocwieja, Tanja (American Society for Microbiology, 2013)
TRIF is an adaptor molecule important in transducing signals from intracellularly signaling Toll-like receptor 3 (TLR3) and TLR4. Recently, TLR2 was found to signal from intracellular compartments. Using a synthetic ligand for TLR2/1 heterodimers, as well as Borrelia burgdorferi, which is a strong activator of TLR2/1, we found that TLR2 signaling can utilize TRIF. Unlike TRIF signaling by other TLRs, TLR2-mediated TRIF signaling is dependent on the presence of another adaptor molecule, MyD88. However, unlike MyD88 deficiency, TRIF deficiency does not result in diminished control of infection with B. burgdorferi in a murine model of disease. This appears to be due to the effects of MyD88 on phagocytosis via scavenger receptors, such as MARCO, which are not affected by the loss of TRIF. In mice, TRIF deficiency did have an effect on the production of inflammatory cytokines, suggesting that regulation of inflammatory cytokines and control of bacterial growth may be uncoupled, in part through transduction of TLR2 signaling through TRIF.